2010
DOI: 10.4012/dmj.2009-082
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and differentiation potential of pluripotent mesenchymal precursor C2C12 cells on resin-based restorative materials

Abstract: This study investigated the proliferation and differentiation potential of pluripotent mesenchymal cells on three resin-based restoratives using a typical pluripotent mesenchymal precursor cell line, C2C12. C2C12 cells were cultured for 3-21 days on cured specimens of a Bis-GMA/TEGDMA-based composite resin (APX; Clearfil AP-X), a 4-META/MMA-based resin cement (SB; Superbond C&B) or a HEMA-containing resin modified glass-ionomer (LC; Fuji Ionomer Type II LC). To examine the influences on differentiation potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The Fuji I and Fuji II eluates were slightly less cytotoxic, suggesting better biocompatibility. Our results are in agreement with previous reports showing that GICs are toxic to dental pulp [16] and pluripotent mesenchymal precursor cells [17].…”
Section: Discussionsupporting
confidence: 94%
“…The Fuji I and Fuji II eluates were slightly less cytotoxic, suggesting better biocompatibility. Our results are in agreement with previous reports showing that GICs are toxic to dental pulp [16] and pluripotent mesenchymal precursor cells [17].…”
Section: Discussionsupporting
confidence: 94%
“…In particular, several clinical studies reported the successful reconstruction of fractured roots with 4-META/MMA-based adhesive resin [7779], which showed good bonding ability in a wet environment and high compatibility with osteoblasts or mesenchymal precursor cells [80,81]. However, none of the present adhesives available on the market promote tissue healing.…”
Section: Addition Of Growth Factorsmentioning
confidence: 99%
“…However, the term multipotency is not adequate to describe the high differentiation ability of these cells, which are able to generate cells representative of all three germ layers. In fact, such cells are often called ‘pluripotent’ to describe their high differentiation ability (56–59). Furthermore, generation of germ line transmitting chimeras are not possible in the case of human cells.…”
Section: Pluripotent Stem Cells Are Present In Mesenchymal Cellsmentioning
confidence: 99%